Extraordinary Molecular Evolution in the PRDM9 Fertility Gene - Thomas, James H.; Emerson, Ryan O.; Shendure, Jay (PloS one, 2009)
Recent work indicates that allelic incompatibility in the mouse PRDM9 (Meisetz) gene can cause hybrid male sterility, contributing to genetic isolation and potentially speciation. The only phenotype of mouse PRDM9 knockouts is a meiosis I block that causes sterility in both sexes. The PRDM9 gene encodes a protein with histone H3(K4) trimethyltransferase activity, a KRAB domain, and a DNA-binding domain consisting of multiple tandem C2H2 zinc finger (ZF) domains. We have analyzed human coding polymorphism and interspecies evolutionary changes in the PRDM9 gene. The ZF domains of PRDM9 are evolving very rapidly, with compelling evidence of positive selection in primates. Positively selected amino acids are predominantly those known to make nucleotide specific contacts in C2H2 zinc fingers. These results suggest that PRDM9 is subject to recurrent selection to change DNA-binding specificity. The human PRDM9 protein is highly polymorphic in its ZF domains and nearly all polymorphisms affect the same nucleotide contact residues that are subject to positive selection. ZF domain nucleotide sequences are strongly homogenized within species, indicating that interfinger recombination contributes to their evolution. PRDM9 has previously been assumed to be a transcription factor required to induce meiosis specific genes, a role that is inconsistent with its molecular evolution. We suggest instead that PRDM9 is involved in some aspect of centromere segregation conflict and that rapidly evolving centromeric DNA drives changes in PRDM9 DNA-binding domains.